Comparative Analysis of Nested Domain Sensitivity on Thunderstorm Simulation using WRF-ARW Model: A Case Study Over Bangladesh - Rahman, Md Mijanur; Mallik, Muhammad Abul Kalam; Samad, Md Abdus (Review of Environment and Earth Sciences, 2021)
Several thunderstorm indicators (TI) and thermodynamic features were evaluated and compared by simulating a thunderstorm (TS) event over Sylhet (24.89° N, 91.86° E), Bangladesh that occurred from 1429 UTC to 1441 UTC on 29 March 2018 using the Advanced Research dynamics solver of Weather Research and Forecasting model (WRF-ARW). The model was run to conduct a simulation for 36 hours utilizing six-hourly Global Final Analysis (FNL) datasets from 0600 UTC of 29 March 2018 to 1200 UTC of 30 March 2018 as initial and lateral boundary conditions. The domain was nested in two different ways: (a) two domains of 15 and 3 km horizontal resolution, and (b) three domains of 12, 6 and 3 km horizontal resolution. These domains were nested with varying outer-domain horizontal grid spacing but a constant 3km inner-domain resolution in order to reasonably verify the effect of nesting on the approximation of the thermodynamic indicators by WRF-ARW. The model outputs were generated with a 10-minute interval for the innermost domain. These outputs were analyzed numerically and graphically using Grid Analysis and Display System (GrADS). Model evaluations of mean sea level pressure (MSLP), maximum and minimum temperature, relative humidity (RH) and 24-hour rainfall were compared with available observational data obtained from Bangladesh Meteorological Department (BMD) to validate the model performance in each case. Based on the analyses and comparisons, it is found that the estimated values in the case of three-way nesting were better indicators of the likelihood of a TS event over that area.